2008
DOI: 10.1086/528377
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-6-Phosphate Dehydrogenase Deficiency Enhances Human Coronavirus 229E Infection

Abstract: The host cellular environment is a key determinant of pathogen infectivity. Viral gene expression and viral particle production of glucose-6-phosphate dehydrogenase (G6PD)-deficient and G6PD-knockdown cells were much higher than their counterparts when human coronavirus (HCoV) 229E was applied at 0.1 multiplicity of infection. These phenomena were correlated with increased oxidant production. Accordingly, ectopic expression of G6PD in G6PD-deficient cells or addition of antioxidant (such as alpha-lipoic acid) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
146
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(153 citation statements)
references
References 15 publications
7
146
0
Order By: Relevance
“…According to our findings, this form binds to ssRNA more tightly than does the reduced form, and could therefore promote replication of the viral genome. This speculation is supported by the recent report by Wu et al 58 who have shown that oxidative stress in the host cell promotes HCoV-229E infectivity. Very likely, SARS-CoV will also induce oxidative stress in the infected host cell, 59 even though its Nsp9 does not seem to form disulfide-linked dimers, at least not in vitro.…”
Section: Discussionmentioning
confidence: 56%
“…According to our findings, this form binds to ssRNA more tightly than does the reduced form, and could therefore promote replication of the viral genome. This speculation is supported by the recent report by Wu et al 58 who have shown that oxidative stress in the host cell promotes HCoV-229E infectivity. Very likely, SARS-CoV will also induce oxidative stress in the infected host cell, 59 even though its Nsp9 does not seem to form disulfide-linked dimers, at least not in vitro.…”
Section: Discussionmentioning
confidence: 56%
“…The milieu inside or at the surface of these vesicles is unknown, but it is well possible that it is partially oxidative. It has also been speculated [25] that formation of disulfide bonds may be a way for the coronaviral Nsps to function in the presence of the oxidative stress that is the consequence of the viral infection [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…5, 6, 7, 8, 9 However, during the past decade, accumulating evidence has demonstrated that G6PD deficiency also affects nucleated cells 10, 11, 12, 13, 14 and cellular pathophysiological events, including dysregulated cell proliferation, accelerated cellular senescence, enhanced susceptibility to viral infection, and impaired embryonic development. 15, 16 G6PD is essential for normal cell growth and survival. For example, G6PD-deficient fibroblasts exhibit retarded growth and premature senescence.…”
mentioning
confidence: 99%